2019
DOI: 10.1021/acs.inorgchem.9b00292
|View full text |Cite
|
Sign up to set email alerts
|

2D Molecular Superconductor to Insulator Transition in the β′′-(BEDT-TTF)2[(H2O)(NH4)2M(C2O4)3]·18-crown-6 Series (M = Rh, Cr, Ru, Ir)

Abstract: The series of salts β"-(BEDT-TTF)2[(H2O)(NH4)2M(C2O4)3].18-crown-6 show ambient-pressure superconductivity when M = Cr or Rh. Evidence indicates that the previously reported Cr and Rh salts show a bulk Berezinski-Kosterlitz-Thouless superconducting transition. The isostructural ruthenium and iridium salts are reported here. The Ir salt represents the first radical-cation salt to contain a 5d tris(oxalato)metallate anion. Both the Ru and Ir salts do not show superconductivity but instead undergo a broad chemica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 35 publications
(70 reference statements)
0
7
1
Order By: Relevance
“…In Fig. 8, we present the plot of m * and the SdH frequency F of β ′′ -(BEDT-TTF) 2 SF 5 CH 2 CF 2 SO 3 (T c : ∼5.2 K, m * : ∼1.9m e , F : ∼200 T) [35] and [36,37] with the results of the present salts. It is clearly found that the parameters of the two salts fall in the correlation derived from our results.…”
mentioning
confidence: 55%
“…In Fig. 8, we present the plot of m * and the SdH frequency F of β ′′ -(BEDT-TTF) 2 SF 5 CH 2 CF 2 SO 3 (T c : ∼5.2 K, m * : ∼1.9m e , F : ∼200 T) [35] and [36,37] with the results of the present salts. It is clearly found that the parameters of the two salts fall in the correlation derived from our results.…”
mentioning
confidence: 55%
“…We recently published a 2 : 1 salt, b 00 -(BEDT-TTF) 2 [(H 2 O)(NH 4 ) 2 Ir(C 2 O 4 ) 3 ]Á18-crown-6, which was the first example in this family to contain a 5d tris(oxalato)metallate anion. 18 A 4 : 1 BEDT-TTF salt has previously been reported with 5d bis(oxalato)platinate, Pt(C 2 O 4 ) 2 2À , which shows metallic behaviour down to 60 K. 26 When using benzonitrile with tris(oxalato)iridate in salt 5 we have also used halobenzenes with tris(oxalato)iridate but no crystals could be obtained, in contrast to the relative ease with which they can be obtained when using the 3d and 4d tris(oxalato)metallates.…”
Section: Materials Advances Papermentioning
confidence: 99%
“…Interestingly, both salts are metallic at room temperature but show metalinsulator transitions at 190 and 240 K, respectively. [36], Ru (66) [36], Cr (67) [37] and Rh (69) [38] (Table 3). The structure resembles that of the previously described compounds β"-(ET) The Cr and Rh salts are superconductors with T c = 4.0-4.9 K and 2.7 K, respectively [37,38].…”
Section: Other Phases With Bedt-ttf and Oxalato Complexesmentioning
confidence: 99%
“…The Ir and Ru salts are not superconductors due to the shorter inter-layer M-M distance (worse 2D systems). The M-I transition in these salts may originate from changes in the anionic layer which induce changes in the BEDT-TTF layer, although Berezinski-Kosterlitz-Thouless (BKT) effects are not discarded [36]. The Ir salt is the first radical salt with a 5d tris(oxalato)metalate anion [36].…”
Section: Other Phases With Bedt-ttf and Oxalato Complexesmentioning
confidence: 99%
See 1 more Smart Citation